PENGARUH PENGALAMAN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA BAGIAN PEMBANGUNAN SEKRETARIAT KABUPATEN KUTAI TIMUR - Heriyanto, Novi Yulianti, H. Eddy Soegiarto K (EKONOMIA, 2015)
The study aims to determine the effect of work experience and motivation on employee performance. Specifically this study aims to find out how the effect of work experience on employee performance and determine how well the effect of motivation on employee performance, as well as to determine the effect of work experience and motivation at the same time the performance of employees in the Secretariat of the Development Section of East Kutai. In this study, the central issue is whether there is influence of work experience and motivation to employee performance at the Secretariat of the Development Section of the East Kutai Regency partially or simultaneously.The analytical method used in this research is descriptive analysis method and quantitative analysis with multiple linear regression analysis. The population in this study are all Employees In The Development Secretariat of the East Kutai Regency which amounted to 40 employees. The sample in this study using a sampling method saturated consisting of 40 Employees In The East Kutai District Development Secretariat.The results showed that the work experience and motivation in a positive and significant effect on the performance of employees in the Secretariat of the Development Section of East Kutai. Based on the results of the coefficient of determination that the relationship Y variable (performance) is influenced strongly by the variable X1 (work experience) and X2 (motivation) amounted to 91.9% and the remaining 8.1% is influenced by other factors not examined in this study , Partial test variable work experience (X1) on employee performance (Y) based on the results obtained by analysis of t count equal to 9.886 with a significant (0.00> 0.05) so that there are positive influence and significant between work experience and performance of employees and the motivation variable (X2) on the performance employees (Y) based on the results obtained by analysis of 3,139 t value and significant positive effect it can be seen from the significant value (0.003 <0.05), which means that if the motivation improved the performance of employees will increase. Partial assay results indicate that the work experience variable most dominant influence employee performance on the part of the Secretariat of the East Kutai Regency Development.